Social carry-over effects on non-social behavioral variation: mechanisms and consequences - Niemelä, Petri T.; Santostefano, Francesca (Frontiers in Ecology and Evolution, 2015)
The field of animal personality is interested in decomposing behaviors into different levels of variation, with its present focus on the ecological and evolutionary causes and consequences of expressed variation. Recently the role of the social environment, i.e. social partners, has been suggested to affect behavioral variation and induce selection on animal personality. Social partner effects exist because characters of social partners (e.g. size, behavior), affect the behavioral expression of a focal individual. Here, we 1) first review the proximate mechanisms underlying the social partner effects on behavioral expression and the timescales at which such effects might take place. We then 2) discuss how within- and among-individual variation in single behaviors and covariation between multiple behaviors, caused by social partners, can carry-over to non-social behaviors expressed outside the social context. Finally, we 3) highlight evolutionary consequences of social carry-over effects to non-social behaviors and 4) suggest study designs and statistical approaches which can be applied to study the nature and evolutionary consequences of social carry-over effects on non-social behaviors. Understanding the proximate mechanisms underpinning the social partner effects is important since it opens a door for deeper understanding of how social environments can affect behavioral variation and covariation at multiple levels, and the evolution of non-social behaviors (i.e. exploration, activity, boldness) that are affected by social interactions.